2010
DOI: 10.1246/bcsj.20090209
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Spectroscopic Characteristics of a Proton-Conductive Ionic Liquid Diethylmethylammonium Trifluoromethanesulfonate [dema][TfOH]

Abstract: Structural specificity including dynamic behavior and stable conformations in the bulk phase of diethylmethylammonium trifluoromethanesulfonate [dema][TfOH], which is assumed to be a prominent ionic liquid electrolyte for non-humidified intermediate temperature fuel cells, have been investigated by 1H NMR, IR spectroscopic analyses, and molecular dynamics (MD) simulation. It is found that an N–H proton in [dema][TfOH] is an exchangeable mobile proton which can be substituted by D2O, and free rotation around th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
24
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 25 publications
3
24
0
Order By: Relevance
“…This is also explainable in terms of the number of [dema][TfO] molecules, which are sources of protons, surrounding arginine molecules. As stated already, a [dema][TfO] molecule has a mobile proton; consequently, [dema][TfO] can work as a proton donor. On the other hand, an arginine molecule needs to accept a proton from surrounding molecules or ions to become a protonated arginine molecule.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…This is also explainable in terms of the number of [dema][TfO] molecules, which are sources of protons, surrounding arginine molecules. As stated already, a [dema][TfO] molecule has a mobile proton; consequently, [dema][TfO] can work as a proton donor. On the other hand, an arginine molecule needs to accept a proton from surrounding molecules or ions to become a protonated arginine molecule.…”
Section: Resultsmentioning
confidence: 91%
“…Recently, we have performed SIMS experiments using a PIL, diethylmethylammonium trifluoromethanesulfonate ([dema][TfO]), which has high protonic conductivity even at room temperature . Then, we reported that [dema][TfO] acted effectively as a primary ion beam as well as a liquid matrix to increase protonated secondary ions of arginine .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The 2800 cm −1 peak is due to the stretching of N-H group present in [dema] + ion when it is free while that of at 3067 cm −1 is due to its interaction with [TfO] − ions. The presence of these two peaks suggests a dynamical state of hydrogen bond network in the membranes containing higher concentration of PIL just as in the case of neat PIL [31,32]. This may have a direct influence over proton conductivity in these electrolytes.…”
Section: Infrared Spectroscopy Analysis To Investigate the Interactiomentioning
confidence: 86%
“…It is evident from the figure that at wave number higher than 2700 cm −1 we can see two set of absorption bands in the range around 2660-2880 cm −1 and 3100-2900 cm −1 . The vibration due to CH stretching appears usually in 3100-2900 cm −1 range [25] and stretching vibration bands in this wave number region can be seen in the FT-IR spectra of triethylamine [26]. Where the absorption peaks in 2660-2890 cm −1 range that usually appear for NH stretching of ammonium cation [25] cannot be seen in the triethylamine FT-IR spectra [26].…”
Section: Ft-ir Analysis Of Teasmentioning
confidence: 98%